2014
DOI: 10.1590/1516-3180.20141326t1
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera for treating acute and chronic wounds

Abstract: BACKGROUND: Aloe vera is a cactus-like perennial succulent belonging to the Liliaceae Family that is commonly grown in tropical climates. Animal studies have suggested that Aloe vera may help accelerate the wound healing process. OBJECTIVE: To determine the effects of Aloe vera-derived products (for example dressings and topical gels) on the healing of acute wounds (for example lacerations, surgical incisions and burns) and chronic wounds (for example infected wounds, arterial and venous ulcers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…There was also a significant reduction in mSBI, which can be attributed to the anti‐inflammatory 13 and antibacterial 18 properties of AV. AV accelerates collagen synthesis and promotes wound healing, 19 which can account for the significant PD reduction and significant CAL gain. Gain in CAL was significantly higher with AV LDD at all time intervals, suggesting the regenerative potential of this herbal agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a significant reduction in mSBI, which can be attributed to the anti‐inflammatory 13 and antibacterial 18 properties of AV. AV accelerates collagen synthesis and promotes wound healing, 19 which can account for the significant PD reduction and significant CAL gain. Gain in CAL was significantly higher with AV LDD at all time intervals, suggesting the regenerative potential of this herbal agent.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera (AV) is one such medicinal, a perennial succulent plant belonging to the Xanthorrhoeaceae family with anti‐inflammatory, 13 antioxidant, 14 antibacterial, 15 antiviral, 16 antifungal, 17 and immune‐boosting properties 18 . It also promotes wound healing by accelerating epithelial cell migration and collagen maturation, facilitating tissue restoration 19 . Acemannan, a polysaccharide from AV, has been found to have osteogenic properties 20 .…”
mentioning
confidence: 99%
“…In clinical trials, fresh Aloe vera gel has been shown to promote healing of burns, including radiation burns [12]. Clinical studies further suggest that fresh Aloe vera gel may promote wound healing; however, it should be noted that only fresh gel or preparations containing 10–70% fresh gel are active [18]. Dried or dated preparations are ineffective in either burn or wound healing.…”
Section: Botanical Dietary Supplements In the Usamentioning
confidence: 99%
“…Dried or dated preparations are ineffective in either burn or wound healing. A 2012 systematic review that assessed the clinical trials using Aloe Vera gel for acute and chronic wounds suggested that the clinical trial data are in general of poor quality, biased, and conflicted [18]. Aloe vera gel has few adverse reactions and is only contraindicated in cases of known allergy to the Liliaceae [12, 16].…”
Section: Botanical Dietary Supplements In the Usamentioning
confidence: 99%
“…Comunque, nonostante alcuni risultati positivi, l'assenza di un consistente numero di trials clinici condotti con rigore scientifico non consente di consigliare l'uso orale del gel di aloe (Date et al, 2012). Riguardo questa seconda modalità, recenti studi suggeriscono che l'assunzione di aloe gel potrebbe essere di giovamento nei casi di gastrite, nonché nell'abbassare i livelli ematici di glucosio in pazienti diabetici e i livelli di lipidi ematici in pazienti con iperlipidemia.…”
Section: Cancrounclassified